Industrial relations and the efficacy of labor law in an economy overwhelmingly dominated by the informal economy: exploratory research in Senegal - Stoleroff, A. (Global Meeting on Law & Society, 2022)
My inquiry begins with various questions: To what extent can one rely on social regulation by law, namely labor law, in a society whose labor market and economy are overwhelmingly dominated by informal work-employment? In other words, how relevant or effective is labor law under these conditions? Does it make sense to do labor market research in terms of the analytical frameworks of 'industrial relations' approaches that concern nation-states and institutional formations predicated in the formal economy and the at least partial orientation of actors in conformity with rules derived from labor legislation and labor law? The empirical reference of my research is West Africa, namely Senegal, where, according to the ILO, 97% of its employment is in the informal economy. While a fraction of employment in its formal economy may fall under labor law and joint regulation of the parties (collective bargaining), what will be the capacity of representative interest actors (particularly unions) to gain recognition by employers and the state, organize members, and build durable organizations that can fulfill bargaining functions? What will be the influence of labor law on the relationships eventually established between the parties? I hypothesize that industrial relations may develop appreciably in large organizations of the formal economy due to their institutional sealing off from the pressures of the informal economy, although they remain a residual niche of the economy and limit their overall significance. The discussion will be based on a survey conducted in Dakar in December 2021 based on document analysis and exploratory interviews with representatives of national and international organizations in this field.